Assessing DNP impact Using program evaluations to capture healthcare system change. Issue 4 (17th April 2016) - Pritham, Ursula A.; White, Patricia
Abstract : Abstract: The doctor of nursing practice (DNP) degree was formalized in 2004. Data evaluating the impact of DNP-prepared nurses on individual patient care, population health, and healthcare system outcomes are limited. This article demonstrates how the DNP Essentials can be used to frame DNP program evaluation data. Abstract : The doctor of nursing practice (DNP) degree was formalized in 2004. Data evaluating the impact of DNP-prepared nurses on individual patient care, population health, and healthcare system outcomes are limited. This article demonstrates how the Essentials of Doctoral Education for Advanced Nursing Practice can be used to frame DNP program evaluation data.